The pharmacist as a public health resource: Expanding telepharmacy services to address social determinants of health during the COVID-19 pandemic - Melanie Livet; Jordana M. Levitt; Alyssa Lee; Jon Easter (Exploratory Research in Clinical and Social Pharmacy, 2021)
Background: The advent of COVID-19 exacerbated the impact of social determinants of health (SDOH) on patients' ability to manage their health, especially those with chronic conditions. Clinical pharmacists are well positioned to expand the patient care services they already provide to address patients' basic social needs, which may otherwise impede medication access and adherence. Objectives: The purpose of this exploratory study was to evaluate the feasibility of expanding a comprehensive medication management (CMM) telepharmacy service to include SDOH support. This service was offered as part of four primary care clinics in rural and underserved North Carolina communities. More specifically, the study aimed to describe the expanded service, evaluate stakeholders' experience with the service, and assess short-term impact on patients with diabetes. Methods: Data collected over the first 4 months of implementation included administrative data used to describe the expanded service; a clinic survey and interviews to assess clinic team members' experience with the service; and patient surveys to evaluate patient satisfaction, as well as impact on SDOH self-efficacy and diabetes quality of life. Results: Through SDOH screening, the pharmacist identified 26 unresolved COVID-prompted SDOH concerns across 66 patients. These concerns were addressed by the pharmacist through three types of brief interventions, including information provision/education (71%), access to resources (21%), and additional care coordination (7%). Clinic team members perceived the expanded service as highly satisfactory and beneficial. Patients also reported high levels of satisfaction and significantly increased their SDOH self-efficacy and diabetes quality of life as a result of the service. Conclusion: These data provide preliminary insights into the expanded role that pharmacists can play to address current population health gaps that can directly impact patients' engagement with their medication regimen and overall health status.